Penatalaksanaan Holistik Pasien Skabies Pada Anak Dengan Hygiene Kurang Baik Di Puskesmas Hanura Melalui Pendekatan Kedokteran Keluarga - Muhammad Muizzulatif; Dian Isti Angraini (MAJORITY, 2021)
Scabies is a skin disease caused by the mite Sarcoptei scabei hominis variety. This disease is a public health problem, especially in tropical and subtropical climates. According to the World Health Organization (WHO), globally it is estimated that as many as 300 million people are currently infected with scabies with a prevalence ranging from 0,2% to 71%. Scabies attacks in groups. Because easy transmission occurs through skin contact either directly or indirectly. Appropriate holistic management using a family medicine approach is needed to achieve therapeutic success and prevent transmission to the community. Patient R, a male student aged 10 years, complained of itching between the fingers, especially at night, since 3 weeks ago. Internal risks in the form of lack of personal hygiene, lack of knowledge, curative treatment patterns, and early adolescence. External risks include similar complaints in the surrounding environment, poor family hygiene, humid houses and poor ventilation, low socioeconomic status, lack of family knowledge. A holistic and comprehensive management effort uses a family medicine approach in the form of education about the causes, transmission, treatment and prevention of disease. The results obtained in the form of a better understanding of the disease and changes in behavior that have an impact on the success of therapy. Holistic management with a family medicine approach is needed for patients with scabies to identify problems in various aspects in order to support the success of therapy and prevent transmission.